41. PROGNOSTIC VALIDATION OF THE EANO ESMO CLASSIFICATION OF LEPTOMENINGEAL METASTASIS. (4th August 2020) - Le Rhun, Emilie; Devos, Patrick; Weller, Johannes; Seystahl, Katharina; Mo, Francesca; Compter, Annette; Sophie Berghoff, Anna; Jongen, Joost; Wolpert, Fabian; Rudà, Roberta; Brandsma, Dieta; van den Bent, Martin; et al.
Abstract: BACKGROUND: The EANO ESMO guidelines have proposed a classification of leptomeningeal metastases (LM) based on clinical (typical/atypical), cytological (positive/negative/equivocal) and MRI (A linear, B nodular, C linear and nodular, D normal or hydrocephalus only) presentation. Type I LM is defined by the presence of tumor cells in the cerebrospinal fluid (CSF) (confirmed LM) whereas type II LM is defined by typical clinical and MRI signs (probable or possible LM). Here we explored the clinical utility of these EANO ESMO LM subtypes. PATIENTS AND METHODS: We retrospectively assembled data from 254 patients with newly diagnosed LM from different solid tumors, including as main primary tumors breast cancer (n=98, 45%), lung cancer (n=65, 25.5%) and melanoma (n=51, 13.5%). Survival curves were estimated using the Kaplan-Meier method and compared by Log-rank test. RESULTS: Median age at LM diagnosis was 56.5 years (range 20–82 years). Typical clinical LM symptoms or signs were noted in 225 patients (88.5%); only 13 patients (5%) were clinically asymptomatic. The most common MRI subtype was A seen in 117 patients (46%). Types B (n=33, 13%), C (n=54, 21%) and D (n=50, 19.5%) were less common. Tumor cells were observed in the CSF in 186 patients (73%) whereas the CSF was equivocal in 24 (9.5%) and negative in 44 (17.5%) patients. Patients with confirmed LM had inferior outcome than patients with probable or possible LM (p=0.0063). Type I patients had inferior outcome than type II patients (p=0.0019). Nodular disease was a negative prognostic factor in type II LM, but not in type I LM (p=0.0138). CONCLUSION: The presence of tumor cells in the CSF appears to have a greater prognostic role than the neuroimaging presentation. EANO ESMO LM subtypes are highly prognostic and should be considered in the design of clinical trials.